1997
DOI: 10.1038/387520a0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between ATM protein and c-Abl in response to DNA damage

Abstract: The gene mutated in the autosomal recessive disorder ataxia telangiectasia (AT), designated ATM (for 'AT mutated'), is a member of a family of phosphatidylinositol-3-kinase-like enzymes that are involved in cell-cycle control, meiotic recombination, telomere length monitoring and DNA-damage response. Previous results have demonstrated that AT cells are hypersensitive to ionizing radiation and are defective at the G1/S checkpoint after radiation damage. Because cells lacking the protein tyrosine kinase c-Abl ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
328
1
3

Year Published

1998
1998
1999
1999

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 448 publications
(338 citation statements)
references
References 18 publications
6
328
1
3
Order By: Relevance
“…ATM is required for the e cient activation of c-Abl by IR (Shafman et al, 1997;Baskaran et al, 1997). The SH3 domain of c-Abl interacts with a proline-rich motif in ATM (Shafman et al, 1997), and the ATMkinase domain was shown in vitro to phosphorylate cAbl on Ser-465 (Baskaran et al, 1997).…”
Section: Responses Mediated By Jnk and C-ablmentioning
confidence: 99%
See 1 more Smart Citation
“…ATM is required for the e cient activation of c-Abl by IR (Shafman et al, 1997;Baskaran et al, 1997). The SH3 domain of c-Abl interacts with a proline-rich motif in ATM (Shafman et al, 1997), and the ATMkinase domain was shown in vitro to phosphorylate cAbl on Ser-465 (Baskaran et al, 1997).…”
Section: Responses Mediated By Jnk and C-ablmentioning
confidence: 99%
“…The SH3 domain of c-Abl interacts with a proline-rich motif in ATM (Shafman et al, 1997), and the ATMkinase domain was shown in vitro to phosphorylate cAbl on Ser-465 (Baskaran et al, 1997). ATM is also required for c-Abl-mediated assembly of the Rad51 repair protein complex following IR .…”
Section: Responses Mediated By Jnk and C-ablmentioning
confidence: 99%
“…The ®nding that c-Abl is present near the ends of certain pachytene chromosomes raises the possibility that c-Abl is involved in telomere movement. In this context, recent studies have demonstrated that c-Abl interacts with ATM (Baskaran et al, 1997;Shafman et al, 1997). ATM, a homolog of the yeast TEL1 (Greenwell et al, 1995), has been found to in¯uence telomeric associations and control telomere length in mammalian cells (Smilenov et al, 1997).…”
Section: (And Data Not Shown)mentioning
confidence: 99%
“…Activation of DNA ± PK by DNA damage results in phosphorylation of c-Abl and induction of c-Abl activity . Other studies have demonstrated that c-Abl associates with the ataxia telangiectasia mutated (ATM) gene product and that ATM may activate c-Abl in the response to DNAdamaging agents (Baskaran et al, 1997;Shafman et al, 1997). Cells de®cient in c-Abl are resistant to DNAdamage-induced apoptosis , while DNA ± PK or ATM-de®cient cells are hypersensitive to radiation (Jeggo et al, 1995;Roth et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…DNA damage-induced activation of cAbl is mediated in part by the DNA-dependent protein kinase (DNA-PK) and the product of the ataxia telangiectasia gene (ATM), both sensors of DNA damage (Baskaran et al, 1997;Kharbanda et al, 1997;Shafman et al, 1997). c-Abl interacts with the p53 tumor suppressor and contributes to p53-dependent Gl phase growth arrest and induction of apoptosis (Goga et al, 1995a;Sawyers et al, 1994;Yuan et al, 1996aYuan et al, ,b, 1997.…”
Section: Introductionmentioning
confidence: 99%